The Neuron Navigators: Structure, function, and evolutionary history - Powers, Regina M.; Hevner, Robert F.; Halpain, Shelley (Frontiers in Molecular Neuroscience, 2023)
Neuron navigators (Navigators) are cytoskeletal-associated proteins important for neuron migration, neurite growth, and axon guidance, but they also function more widely in other tissues. Recent studies have revealed novel cellular functions of Navigators such as macropinocytosis, and have implicated Navigators in human disorders of axon growth. Navigators are present in most or all bilaterian animals: humans have three Navigators (NAV1-3), Drosophila has one (Sickie), and C. elegans has one (Unc-53). Structurally, Navigators have conserved N- and C-terminal regions each containing specific domains. The N-terminal region contains a calponin homology (CH) domain and one or more SxIP motifs, thought to interact with the actin cytoskeleton and mediate localization to microtubule plus-end binding proteins, respectively. The C-terminal region contains two coiled-coil domains, followed by a AAA+ family nucleoside triphosphatase domain of unknown activity. The Navigators appear to have evolved by fusion of N- and C-terminal region homologs present in simpler organisms. Overall, Navigators coordinate the cytoskeletal response to extracellular cues via microtubules and actin filaments, in conjunction with membrane trafficking. We propose that uptake of fluid-phase cues and nutrients and/or downregulation of cell surface receptors could represent general mechanisms that explain Navigator functions. In future studies, more can be learned about the Navigator functions by developing new models, including conditional knockout mice and patient-derived human cerebral organoids. Importantly, further biochemical studies are needed to define the activities of the Navigator AAA+ domain, and to study potential interactions among different Navigators and their binding partners.